Cold sintering-enabled interface engineering of composites for solid-state batteries - Nie, Bo; Liu, Tengxiao; Alcoutlabi, Mataz; Basu, Saurabh; Kumara, Soundar; Li, Mingxin; Lian, Jie; Sun, Hongtao (Frontiers in Energy Research, 2023)
The cold sintering process (CSP) is a low-temperature consolidation method used to fabricate materials and their composites by applying transient solvents and external pressure. In this mechano-chemical process, the local dissolution, solvent evaporation, and supersaturation of the solute lead to “solution-precipitation” for consolidating various materials to nearly full densification, mimicking the natural pressure solution creep. Because of the low processing temperature (<300 ºC), it can bridge the temperature gap between ceramics, metals, and polymers for co-sintering composites. Therefore, CSP provides a promising strategy of interface engineering to readily integrate high-processing temperature ceramic materials (e.g., active electrode materials, ceramic solid-state electrolytes) as “grains” and low-melting-point additives (e.g., polymer binders, lithium salts, or solid-state polymer electrolytes) as “grain boundaries.” In this minireview, the mechanisms of geomimetics CSP and energy dissipations are discussed and compared to other sintering technologies. Specifically, the sintering dynamics and various sintering aids/conditions methods are reviewed to assist the low energy consumption processes. We also discuss the CSP-enabled consolidation and interface engineering for composite electrodes, composite solid-state electrolytes, and multi-component laminated structure battery devices for high-performance solid-state batteries. We then conclude the present review with a perspective on future opportunities and challenges.